Dollar store policy opportunities in Baltimore City: community member and policy maker perspectives - Sundermeir, Samantha M.; Santos, Sydney R.; Lewis, Emma C.; John, Sara; Gardner, Karen; Friedman, Emily; Poirier, Lisa; Hua, Shuxian; Peoples-Brown, Sevetra; Benjamin-Neelon, Sara E.; Gittelsohn, Joel (Frontiers in Nutrition, 2024)
Introduction There are currently over 50 dollar stores in Baltimore City, Maryland. Community perceptions of over-saturation and resulting neighborhood impacts have garnered recent attention. A Maryland State Senate Bill required further study of dollar stores in Baltimore City to inform future policy. Therefore, the over-arching goal of this study was to generate community-informed policy recommendations for the Baltimore City Council. Methods Three methods of data collection were used: (1) in-depth interviews with community members, retail staff/owners, dollar store staff, and policy makers; (2) an online survey of Baltimore City residents; and (3) workshop with community members and one with policy makers. Triangulation across data sources, discussion amongst the research team, and member checking were used to generate the top four policy options: a conditional use ordinance, a community benefits agreements, a dispersal ordinance, and a staple foods ordinance. Results There was strong support for policies that encourage dollar stores to better align with community priorities (e.g., improving store cleanliness and appearance, increasing availability of healthy foods), as opposed to closing or banning dollar stores entirely. There was also strong support for policies that would empower communities to participate in determining the role of dollar stores in their neighborhoods, for example through a conditional use ordinance or community benefits agreement. Key concerns included policy enforcement, given the additional funding required, and current limited capacity at the city government level. Strategies to address such challenges were generated including implementing business licenses at the city level, linking new ordinances to dollar store leases and permits, and encouraging dollar store participation in federal and local programs to more feasibly stock healthier food items (e.g., fresh produce). Dissatisfaction was expressed regarding a lack of policy options to address the existing dollar stores, not just new dollar stores entering the City. Discussion This study is the first of its kind to assess community support for dollar store policies at the local level, and serves to inform policies that improve dollar stores. A report of these findings was provided to Baltimore City Council to inform new, community-supported dollar store policies.